Spies in disguise [videorecording (DVD)] (20th Century Fox Home Entertainment, 2020)
Super spy Lance Sterling and scientist Walter Beckett are almost exact opposites. Lance is smooth, suave, and debonair. Walter is not. But when events take an unexpected turn, this unlikely duo is forced to team up for the ultimate mission that will require an almost impossible disguise, transforming Lance into the brave, fierce, majestic pigeon. Walter and Lance suddenly have to work as a team, or the whole world is in peril.